E-Government, Governance and Corruption in Asian countries - Suardi, Imelda (Emerging Markets : Business and Management Studies Journal, 2021)
In developing countries, the implementation of e-government is at greater risk of failure when the corruption is still high. This paper examines the effect of e-government on the level of corruption in 47 developing countries in Asia using E-Government Development Index which is divided into components of online service, human capital, telecommunication infrastructure and e-participation. This paper also places the role of governance in government to moderate the relationship between e-government and perceptions of corruption. The result shows that implementation of e-government and governance has increased the perception of corruption with telecommunications infrastructure has the most significant effect.